ANALISIS PRESTASI KERJA PEGAWAI (Studi Pada Dinas Perindustrian dan Perdagangan Kabupaten Kutai Timur) - Susiati, Susiati (PREDIKSI, 2016)
This study aims to determine and describe the level of job performance of employees at the Office of Industry and Commerce of East Kutai. The method used in this research is descriptive qualitative.The results showed that the job performance of employees in the Office of Industry and Commerce of East Kutai included in either category. From the analysis, the hypothesis formulated in this study, namely: